Conceitos e ferramentas para uma criação musical hipermidiática: o caso 5 elementos - Leandro Pereira de Souza (2014)
This paper focuses on the relationships between digital technologies and musical creation, discussing some key concepts and ideas such as cyberculture,digital micro-integration, digital perception and hypermedia / hypertext. Based on these concepts and ideas, a conceptual tool is proposed, which explores the characteristics of a hypermedia / hypertext in the music creation process. We analyse compositional elements of works on which it was possible to observe hypertext features. a piece developed from the proposed conceptual tool, called 5 elementos, is also presented and discussed.